2003
DOI: 10.1152/ajpgi.00508.2002
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17β-D-glucuronide induces endocytic internalization of Bsep in rats

Abstract: Endocytic internalization of the multidrug resistance-associated protein 2 (Mrp2) was previously suggested to be involved in estradiol-17β-d-glucuronide (E217G)-induced cholestasis. Here we evaluated in the rat whether a similar phenomenon occurs with the bile salt export pump (Bsep) and the ability of DBcAMP to prevent it. E217G (15 μmol/kg iv) impaired bile salt (BS) output and induced Bsep internalization, as assessed by confocal microscopy and Western blotting. Neither cholestasis nor Bsep internalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 43 publications
10
140
0
2
Order By: Relevance
“…However, functional analysis of canalicular vesicles isolated from the liver of rats treated with ethinyl-estradiol showed a marked reduction of ATP-dependent taurocholate transport activity, suggesting a role of posttranslational processes in this model of cholestasis [26]. Supporting this assumption, relocation of Bsep into subapical vesicles has been observed in rats with estradiol-17β-glucuronide induced cholestasis [53]. Internalization of Bsep was also observed in rats treated with lithocholate and taurolithocholate, which can be prevented by preadministration of cAMP [52,54] or of tauroursodeoxycholate [62].…”
Section: Pathophysiologymentioning
confidence: 95%
“…However, functional analysis of canalicular vesicles isolated from the liver of rats treated with ethinyl-estradiol showed a marked reduction of ATP-dependent taurocholate transport activity, suggesting a role of posttranslational processes in this model of cholestasis [26]. Supporting this assumption, relocation of Bsep into subapical vesicles has been observed in rats with estradiol-17β-glucuronide induced cholestasis [53]. Internalization of Bsep was also observed in rats treated with lithocholate and taurolithocholate, which can be prevented by preadministration of cAMP [52,54] or of tauroursodeoxycholate [62].…”
Section: Pathophysiologymentioning
confidence: 95%
“…The rapid, short-term, adaptation of canalicular ABCB11 expression is mainly regulated at the posttranscriptional level. This regulation involves the shuttling of ABCB11 between its intracellular pool and the canalicular membrane and may be triggered by hormones (Crocenzi et al, 2003), oxidative stress (Pérez et al, 2006), hydration , and cell swelling (Häussinger et al, 1993), as demonstrated in vitro and in rodent studies. Cell swelling can occur in response to a meal and lead to a rapid canalicular insertion of ABCB11, which increases the postprandial excretion of bile acids.…”
Section: Abcb11mentioning
confidence: 99%
“…In the rat model of cholestasis associated with pregnancy (treatment of rats with estradiol), a relocation of Bsep into subapical vesicles is observed [18]. If these rats are treated with 6-ethyl chenodeoxycholate, a potent ligand for FXR, Bsep is induced and the cholestasis induced by estradiol is reversed [27].…”
Section: Pathophysiological Consequences Of Altered Bsep Function Andmentioning
confidence: 99%